Risk Factors in Neuroleptic Malignant Syndrome: A 10-year Case-control Study of Neuroleptic Use in Patients in Charoenkrung Pracharak Hospital - Sarinthip Sirisuwannarat (Siriraj Medical Journal)
Objective: To identify the risk of using high doses of neuroleptics in the development of neuroleptic malignant syndrome (NMS). Additionally, we examined other potential risk factors, including age, psychiatric diagnosis, route of neuroleptic administration, dose escalation over a short period, psychomotor agitation, dehydration, and electrolyte imbalance.